Acupuncture in the Treatment of Resistant Hypertension: A Narrative Review of Efficacy and Safety - Yanasta Yudo Pratama; Vica Hilda Amelia; Muhammad Hamza Mubarak; Muhammad Luthfi Adnan (Pancasakti Journal Of Public Health Science And Research, 2025)
Resistant hypertension (RH) is a critical concern due to persistent uncontrolled blood pressure despite multiple medications, and its association with severe cardiovascular and renal complications. This narrative review aims to critically analyze existing research on acupuncture as an adjunctive treatment for RH, synthesizing evidence on its mechanisms and effects on clinical outcomes like blood pressure control and quality of life. A literature search was conducted from April to May 2025 across Google Scholar, PubMed, and ScienceDirect, using variations of keywords combination: resistant hypertension, acupuncture, electro-acupuncture, management, antihypertension, blood pressure. We found there is limited evidence for acupuncture application for RH management, even application for hypertension has been widely studied. Acupuncture is safety for hypertension management and has limited adverse event. In conclusion, acupuncture is a promising, generally safe complementary treatment for resistant hypertension, offering benefits beyond blood pressure reduction and improving quality of life, particularly for patients facing medication challenges. However, further rigorous, standardized research is needed to fully establish its role alongside conventional therapies.